The Mensheviks : from the revolution of 1917 to the second world war / edited by Leopold H. Haimson ; with contributions by David Dallin... [et al.] ; translated by Gertrude Vakar - Haimson, Léopold H.Dallin, David J. (1889-1962) Vakar, Gertruda (Hoover Institution publications; 117)
En verso de la portada: "This volume is one of a series arising from the work of the Inter-university Project on the History of the Menshevik movement." | Incluye referencias bibliográficas e índice